Novel Synthesis of Some New Fluorescent 2-Amino-3-cyanopyridines - Zonouzi, Afsaneh; Izakian, Zakieh; Ng, Seik Weng (The Japan Institute of Heterocyclic Chemistry, 2012)
Novel synthesis of some new fluorescent 2-amino-3-cyanopyridines 2a-m in the presence of N-hydroxybenzamide or p-toluenesulfonic acid is described. Photophysical data including λ Abs. and λ Flu. of 2a-m in CH 2Cl 2, MeCN and MeOH have been measured. © 2012 The Japan Institute of Heterocyclic Chemistry.